Composite‐Structure Materials for Na‐Ion Batteries. Issue 4 (15th October 2018) - Su, Heng; Yu, Haijun
Abstract: Due to the growing concern of aggravated environmental problems (air pollution, global warming, etc.) and Li resources, Na‐ion batteries have received significant attention as a promising alternative. Many electrode materials for Na‐ion batteries have been reported in the past, especially over the past five years. However, most of these materials have a single crystalline structure and exhibit a limited electrochemical performance. Recently, some electrode materials with composite structures have been reported for both Li‐ion and Na‐ion batteries and have attracted attention because of their enhanced comprehensive electrochemical performance. Herein, a detailed discussion on the development of these composite‐structure materials for Na‐ion batteries is conducted based on the crystalline structure. The structure design, identification, and adjustment of these materials are thoroughly discussed. Furthermore, the future outlook based on a mechanism analysis and a new electrode‐material structure system is also introduced in this work, by reviewing previous important studies on composite‐structure materials. Abstract : Composite‐structure materials are very promising with high electrochemical performance. This review focuses on the most recent works on composite‐structure materials, including structure design, structure ratio adjustment to balance the electrochemical performance, and reaction mechanisms. This work can help researchers design new electrode materials with attractive comprehensive electrochemical performance for advanced battery systems.